(untitled) (Scientific Journal of Research Studies in Future Civil Engineering, 2023)
Paying attention to the regeneration of urban water banks is an important opportunity in cities and has been studied and researched by city managers in recent years. Urban water banks can play an effective role in attracting domestic and foreign tourists, and they also have an effective role on various social and cultural aspects of cities. Urban water banks are usually the main basis of the identity of cities and are used as a part of urban spaces in different parts of the world. In other words, based on the research conducted in this regard, it can be stated that the water banks of the cities are important and important in terms of geographic, natural and human characteristics, and study and review and provide appropriate solutions in relation to The recreation of these banks is a step for the social and cultural growth of people and is important and necessary. The existence of these natural potentials requires more attention and study in order to provide design principles and their optimal use. Therefore, the need for in-depth studies and researches in this area is significantly in the priority of urban management topics.